Mejora de la estabilidad en sistemas eléctricos de distribución mediante el uso de autos eléctricos como fuentes de inyección de energía - Espín Logroño, Andrés Ademar (Universidad Politécnica Salesiana. Carrera de Ingeniería Eléctrica. Sede Quito, 2018)
stability in Electrical Distribution Systems (DS) through the use of Electric Vehicle (EV) batteries charging and discharging systems as sources of energy injection that replace the energy produced by Thermal Generators, to satisfy the needs of the demand, maximizing the efficiency and minimizing the use of resources in peak hours. This is done through the application of the Fuzzy Logic (FL) that defines the possible states of the operation, determining an optimal scenario for: loading times of the EV, times of use of the EV and loading a DS of Injection. The study is supported by mathematical simulation in the software MATLAB and its fuzzy toolbox, allowing to analyze and subsequently optimize the delivery of electrical energy to DS, supporting the case studies discussed in this paper, testing the results of stability and feasibility in the system.